A brief survey of the Bible. discovering the big picutre of God's story from Genesis to Revelation /: discovering the big picutre of God's story from Genesis to Revelation. Study guide : 14 sessions : (2015) - Walton, John H, 1952-; Strauss, Mark L, 1959-
No abstract available